Worauf achten AirBnb Gäste? Eine semantische Analyse von Online-Bewertungen mittels Latent-Dirichlet-Allocation - Dierkes, Lukas

Innovation in Nutzerkommentaren – Eine Analyse am Beispiel einer Rezept-Plattform - Tiggemann, Benjamin

Entwicklung und Pilotierung eines Experiments über Visualisierungen von Taxonomien in der Wirtschaftsinformatik - Rennemeier, Steffen

Determinants of Loyalty in Online Communities: A Systematic Literature Review - Schlesiger, Laura

Konkurrent oder Komplementär? Eine empirische Analyse über das Nutzerverhalten in Online-Communities in Folge einer Smart Product Innovation - Dierkes, Johannes

Raising Money for a Good Cause – An Econometric Analysis of Key Factors to Successful Personal and Charitable Crowdfunding Campaigns - Krüger, Noah

Benchmarking digitaler Gebrauchtgütermärkte - Eine Analyse zur Entwicklung von Best Practices am Beispiel von Miele Professional - Schröder, Felix

„For developers, by developers”? – Analyzing the Impact of Programming Languages’ Major Releases on Online Q&A Behavior - Werner, Timur

Interdependente Geschäftsmodelle: Eine systematische Analyse von Relationen in Geschäftsmodell-Modellierungssprachen - Wittmann, Daniel

Einblicke in explizite und implizite Erwartungen Lehrender an Studierendentexte. Textbasierte Interviews zu Zielen und Erträgen von fachsensiblem Peer-Textfeedback - Karsten, Andrea (Schreiblehrkonzepte an Hochschulen. Fallstudien und Reflexionen zum fachspezifischen Schreibenlehren und -lernen)

(Selbst-)Kritik und (Selbst-)Reflexion. Fragen stellen, Stimmen identifizieren, Referenzpunkte finden. - Karsten, Andrea (JoSch - Journal der Schreibwissenschaft)

Interfacial Covalent Bonds Regulated Electron-Deficient 2D Black Phosphorus for Electrocatalytic Oxygen Reactions - Wang, Xia; Kormath Madam Raghupathy, Ramya; Querebillo, Christine Joy; Liao, Zhongquan; Li, Dongqi; Lin, Kui; Hantusch, Martin; Sofer, Zdeněk; Li, Baohua; Zschech, Ehrenfried; Weidinger, Inez M.; Kühne, Thomas; et al. (Advanced Materials)
Abstract Developing resource-abundant and sustainable metal-free bifunctional oxygen electrocatalysts is essential for the practical application of zinc–air batteries (ZABs). 2D black phosphorus (BP) with fully exposed atoms and active lone pair electrons can be promising for oxygen electrocatalysts, which, however, suffers from low catalytic activity and poor electrochemical stability. Herein, guided by density functional theory (DFT) calculations, an efficient metal-free electrocatalyst is demonstrated via covalently bonding BP nanosheets with graphitic carbon nitride (denoted BP-CN-c). The polarized PN covalent bonds in BP-CN-c can efficiently regulate the electron transfer from BP to graphitic carbon nitride and significantly promote the OOH* adsorption on phosphorus atoms. Impressively, the oxygen evolution reaction performance of BP-CN-c (overpotential of 350 mV at 10 mA cm−2, 90% retention after 10 h operation) represents the state-of-the-art among the reported BP-based metal-free catalysts. Additionally, BP-CN-c exhibits a small half-wave overpotential of 390 mV for oxygen reduction reaction, representing the first bifunctional BP-based metal-free oxygen catalyst. Moreover, ZABs are assembled incorporating BP-CN-c cathodes, delivering a substantially higher peak power density (168.3 mW cm−2) than the Pt/C+RuO2-based ZABs (101.3 mW cm−2). The acquired insights into interfacial covalent bonds pave the way for the rational design of new and affordable metal-free catalysts.
Keywords: 2D materials; bifunctional oxygen electrocatalysts; black phosphorus; oxygen evolution reaction; zinc–air batteries

Thermodynamically stable polymorphs of nitrogen-rich carbon nitrides: a C3N5 study - Ghasemi, Alireza; Mirhosseini, Hossein; Kühne, Thomas (Phys. Chem. Chem. Phys.)
We have carried out an extensive search for stable polymorphs of carbon nitride with C3N5 stoichiometry using the minima hopping method. Contrary to the widely held opinion that stacked{,} planar{,} graphite-like structures are energetically the most stable carbon nitride polymorphs for various nitrogen contents{,} we find that this does not apply for nitrogen-rich materials owing to the high abundance of N–N bonds. In fact{,} our results disclose novel morphologies with moieties not previously considered for C3N5. We demonstrate that nitrogen-rich compounds crystallize in a large variety of different structures due to particular characteristics of their energy landscapes. The newly found low-energy structures of C3N5 have band gaps within good agreement with the values measured in experimental studies.

"Hallo, wer spricht? Hallo, wer spricht!" Über die Poetik der Selbstoptimierung in deutschsprachiger Gegenwartsliteratur - Tönsing, Johanna

Einleitung - Tönsing, Johanna; Bernhardt, Sebastian (Zeit und Zeitnutzung als Motiv in der Kinder- und Jugendliteratur)

Zeitnutzung in der aktuellen Kinder- und Jugendliteratur. Literaturwissenschaftliche und literaturdidaktische Perspektiven

Ungeahnte Perspektiven der Literatur auf die Subjektivierungsfigur der Selbstoptimierung am Beispiel von Bodo Kirchhoffs Body-Building und Elfriede Jelineks Ein Sportstück - Tönsing, Johanna (Optimierung des Selbst. Band zur Abschlusstagung des Graduiertenkollegs Ethnographien des Selbst in der Gegenwart der Universität Mainz)

Ein feministischer Blick: Zur Darstellung der Coronakrise in ausgewählter Kinder- und Jugendliteratur - Tönsing, Johanna (Mitteilungen des deutschen Germanistenverbands 2 (2021). In Krisen erzählen - von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen)

Über das Kotzen in der Literatur. John von Düffels Ego (2003) als Ausverleibung ökonomischer Logiken - Tönsing, Johanna (Öffnung – Schließung – Übertritte. Körperbilder in der deutschsprachigen Gegenwartsliteratur)

John von Düffel´s "Ego" (2001) as a Seismographic Recorder of the Neoliberal Crisis - Tönsing, Johanna (Invested Narratives: German Responses to economic Crisis and Ordnung)

External Focus of Attention Influences Cortical Activity Associated with Single Limb Balance Performance - Sherman, David A; Lehmann, Tim; Baumeister, Jochen; Gokeler, Alli; Donovan, Luke; Norte, Grant E (Physical Therapy)
Abstract Objective External focus (EF) of attention leads to improved balance performance. Consideration of the neuromodulatory effects of EF may inform its clinical utility in addressing neuroplastic impairments after musculoskeletal injuries. We aimed to determine whether electrocortical activity and balance performance changed with attentional foci that prioritized differing sensory feedback and whether changes in electrocortical activity and balance were associated. Methods Individuals who were healthy (n = 15) performed a single-limb balance task under 3 conditions: internal focus (IF), somatosensory focus [EF with a baton (EF-baton)], and visual focus [EF with a laser (EF-laser)]. Electrocortical activity and postural sway were recorded concurrently using electroencephalography and a triaxial force plate. Electroencephalographic signals were decomposed, localized, and clustered to generate power spectral density in θ and α-2 frequency bands. Postural sway signals were analyzed with center-of-pressure sway metrics (eg, area, distance, velocity) and knee angle. The relationship between percent change in clustered brain activity and task performance metrics was assessed. Results Both EF conditions resulted in increased cortical activity and improved balance performance compared to IF. EF-laser had the largest effect, demonstrating increased frontal θ power (d = 0.64), decreased central θ power (d = −0.30), and decreased bilateral motor, bilateral parietal, and occipital α-2 power (d = −1.38 to −4.27) as well as a shorter path distance (d = −0.94) and a deeper (d = 0.70) and less variable (d = −1.15) knee angle than IF. Weak to moderate associations exist between increases in cortical activity and improved balance performance (ρ = 0.405–0.584). Conclusions EF resulted in increased cortical activity associated with cognitive, motor, somatosensory, and visual processing. EF-laser, which prioritized visual feedback, had the largest and broadest effects. Changes in cortical activity resulting from EF were independently associated with improved balance performance. Impact This study demonstrates that goal-oriented attention results in functional increases in brain activity compared to internally directed self-focus. These results suggest EF may target neurophysiologic impairments and improve balance in clinical populations.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Light-responsive polymeric nanoparticles based on a novel nitropiperonal based polyester as drug delivery systems for photosensitizers in PDT - Schoppa, Timo; Jung, Dimitri; Rust, Tarik; Mulac, Dennis; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)

Backbone-Degradable (Co-)Polymers for Light-Triggered Drug Delivery - Rust, Tarik; Jung, Dimitri; Hoppe, Axel; Schoppa, Timo; Langer, Klaus; Kuckling, Dirk (ACS Applied Polymer Materials)

Direct Asymmetric Aldol Reaction in Continuous Flow Using Gel‐Bound Organocatalysts - Schmiegel, Carsten J.; Baier, Rene; Kuckling, Dirk (European Journal of Organic Chemistry)

Altering of lower critical solution temperature of environmentally responsive poly (N-isopropylacrylamide-co-acrylic acid-co-vanillin acrylate) affected by acrylic acid, vanillin acrylate, and post-polymerization modification - Abdelaty, Momen S. A.; Kuckling, Dirk (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Coupling of CO2 and epoxides catalysed by novel N-fused mesoionic carbene complexes of nickel(ii) - Watt, Fabian A.; Sieland, Benedikt; Dickmann, Nicole; Schoch, Roland; Herbst-Irmer, Regine; Ott, Holger; Paradies, Jan; Kuckling, Dirk; Hohloch, Stephan (Dalton Transactions)
Keywords: Inorganic Chemistry

Continuous Flow Synthesis of Azoxybenzenes by Reductive Dimerization of Nitrosobenzenes with Gel‐Bound Catalysts - Schmiegel, Carsten J.; Berg, Patrik; Obst, Franziska; Schoch, Roland; Appelhans, Dietmar; Kuckling, Dirk (European Journal of Organic Chemistry)

Backbone vs. side-chain: two light-degradable polyurethanes based on 6-nitropiperonal - Jung, Dimitri; Rust, Tarik; Völlmecke, Katharina; Schoppa, Timo; Langer, Klaus; Kuckling, Dirk (Polymer Chemistry)

Dually cross-linked single networks: structures and applications - Rodin, Maksim; Li, Jie; Kuckling, Dirk (Chemical Society Reviews)

"There". Die Verwendung von "there" im authentischen Englisch, im Englisch von Lernenden und in Schulbüchern - Mindt, Ilka (Sprachwissenschaft und Fremdsprachendidaktik: Konstruktionen und Konstruktionslernen)

Nowhere-zero 3-flows in toroidal graphs - Li, Jiaao; Ma, Yulai; Miao, Zhengke; Shi, Yongtang; Wang, Weifan; Zhang, Cun-Quan (Journal of Combinatorial Theory, Series B)
Keywords: Computational Theory and Mathematics; Discrete Mathematics and Combinatorics; Theoretical Computer Science

Holistic change propagation and impact analysis in requirements management - Gräßler, Iris; Oleff, Christian; Preuß, Daniel
In developing complex technical systems, requirements are subject to continuous change. Systematic and holistic change impact analysis and proactive measures are required for reducing the number of requirement changes and their negative impact. There is no method to analyse the holistic impact of a requirement change in the context of developing complex technical systems. Holistic analysis requires to consider the local effects of requirement changes as well as effects from change propagation. To develop an approach for holistic change propagation and impact analysis, twelve performance goals are defined. Those are derived from a state of research analysis as well as an industry workshop. A three-step method is proposed. Firstly, requirement dependencies that cause change propagation are detected. Secondly, critical requirements are automatically identified based on a Page Rank algorithm. Thirdly, change impact of critical requirements is analysed based on a guideline. Validation proves that ten goals are fulfilled and two are partly fulfilled. The method addresses major shortcomings of preceding research and enables sound decision making for development engineers both before a change occurs and during decision process on a change request. This helps to reduce negative change impact in development projects and the risk of project failure.

Was treibt die Komplexität der Ertragsbesteuerung multinationaler Unternehmen? – Ergebnisse einer Befragung in der deutschen Finanzverwaltung - Bornemann, Tobias; Schipp, Adrian; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Abweichende steuerliche Verrechnungspreise in der Steuererklärung oder als Ergebnis einer Betriebsprüfung zwischen verschiedenen Staaten - Lorenz, Johannes; Sureth-Sloane, Caren; Diller, Markus

Wie kompliziert darf eine Regel sein? - Sureth-Sloane, Caren; Simons, Dirk (Frankfurter Allgemeine Zeitung)

2020 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Wem nutzt Public Country-by-Country Reporting? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren

Besteuerung und Rechtsformwahl, 8., aktualisierte und erweiterte Auflage - Maßbaum, Alexandra; Sureth-Sloane, Caren

Zur Komplexität des Steuersystems - Sureth-Sloane, Caren (Süddeutsche Zeitung)

Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)
Abstract In this article we combine Debreu’s (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz’s (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu’s concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash’s demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.

Jicer: Simplifying Cooperative Android App Analysis Tasks - Pauck, Felix; Wehrheim, Heike (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

Cryptimeleon: A Library for Fast Prototyping of Privacy-Preserving Cryptographic Schemes - Bobolz, Jan; Eidens, Fabian; Heitjohann, Raphael; Fell, Jeremy

Configurable lossless broadband beam splitters for semi-guided waves in integrated silicon photonics - Hammer, Manfred; Ebers, Lena; Förstner, Jens (OSA Continuum)
We show that narrow trenches in a high-contrast silicon-photonics slab can act as lossless power dividers for semi-guided waves. Reflectance and transmittance can be easily configured by selecting the trench width. At sufficiently high angles of incidence, the devices are lossless, apart from material attenuation and scattering due to surface roughness. We numerically simulate a series of devices within the full 0-to-1-range of splitting ratios, for semi-guided plane wave incidence as well as for excitation by focused Gaussian wave bundles. Straightforward cascading of the trenches leads to concepts for 1×M-power dividers and a polarization beam splitter.
Keywords: tet_topic_waveguide

DeepCoMP: Coordinated Multipoint Using Multi-Agent Deep Reinforcement Learning - Schneider, Stefan Balthasar; Karl, Holger; Khalili, Ramin; Hecker, Artur
Macrodiversity is a key technique to increase the capacity of mobile networks. It can be realized using coordinated multipoint (CoMP), simultaneously connecting users to multiple overlapping cells. Selecting which users to serve by how many and which cells is NP-hard but needs to happen continuously in real time as users move and channel state changes. Existing approaches often require strict assumptions about or perfect knowledge of the underlying radio system, its resource allocation scheme, or user movements, none of which is readily available in practice. Instead, we propose three novel self-learning and self-adapting approaches using model-free deep reinforcement learning (DRL): DeepCoMP, DD-CoMP, and D3-CoMP. DeepCoMP leverages central observations and control of all users to select cells almost optimally. DD-CoMP and D3-CoMP use multi-agent DRL, which allows distributed, robust, and highly scalable coordination. All three approaches learn from experience and self-adapt to varying scenarios, reaching 2x higher Quality of Experience than other approaches. They have very few built-in assumptions and do not need prior system knowledge, making them more robust to change and better applicable in practice than existing approaches.
Keywords: mobility management; coordinated multipoint; CoMP; cell selection; resource management; reinforcement learning; multi agent; MARL; self-learning; self-adaptation; QoE

Self-aware Operation of Heterogeneous Compute Nodes using the Learning Classifier System XCS - Hansmeier, Tim (HEART '21: Proceedings of the 11th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Beep-And-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Algorithms for Sensor Systems (ALGOSENSORS '21))

“Mehr wert als tausend Männer” – Luise Adelgunde Victorie Kulmus Gottsched und die wahre Minerva - Hagengruber, Ruth (Musikwissenschaft der Vielfalt. Festschrift für Rebecca Grotjahn zum 60. Geburtstag)

Out of the Box – into the Green and the Blue - Hagengruber, Ruth (Philosophisches Jahrbuch 128. Jahrgang I/2021)

Philosophinnen an die Macht - Hagengruber, Ruth (Female Recruiting Report (3))

Ökonomie, Technik, Umwelt: Die Zukunft bestimmen, während wir die Vergangenheit überdenken: Defining the Future – Rethinking the Past - Hagengruber, Ruth (Konsens)